A methodological framework for ascertaining the social capital of environmental community organisations in urban Australia - Dhakal, Subas P. (Emerald Group Publishing Limited, 2014)
Purpose – The purpose of this paper is to ascertain the level of social capital in environmental community organisations (ECOs) in Perth, Western Australia. On a general level, social capital in ECOs is understood as intra-organisational and inter-organisational relationships that organisations maintain through interactions. Design/methodology/approach – This paper utilises quantitative (i.e. survey) as well as qualitative (i.e. interviews) approaches to data collection and analysis. It proposes a methodological framework to measure the level of social capital, and explores the association between the ascertained level of social capital and organisational capabilities. Findings – The results of the survey and interviews reveal that while the level of social capital is needs based, maintaining a higher intensity of organisational relationships puts ECOs in a better position to do more with less. Research limitations/implications – The findings advance the task of ascertaining the level of social capital in ECOs from organisational interactions perspective. Originality/value – This paper captures a community organisation-specific methodological framework to measure and analyse social capital.